Cutaneous intralymphatic anaplastic lymphoma kinase‐negative anaplastic large‐cell lymphoma arising in a patient with multiple rounds of breast implants. (22nd December 2020) - Wang, Huan‐You; Thorson, John A.; Hinds, Brian R.; Swalchick, William; Parker, Barbara A.; Chong, Alice; Wallace, Anne M.; Goodman, Aaron M.
Abstract: Primary cutaneous anaplastic large‐cell lymphoma and breast implant‐associated ALCL (BIA‐ALCL) are rare subtypes of anaplastic lymphoma kinase (ALK)‐negative ALCLs originating from skin and breast implants, respectively. Herein, we report a unique case of cutaneous ALK‐negative ALCL occurring in the skin of left medial breast from a patient with multiple rounds of bilateral breast implants and a history of breast carcinoma. The lymphoma cells are entirely confined to the lymphatic channels in the dermis, and the patient has no other areas of skin abnormality, no lymphadenopathy, peri‐implant fluid accumulation, or masses from the bilateral capsules of implants. The differential diagnosis and its relationship with breast implants are further explored.